2004
DOI: 10.1001/jama.291.15.1841
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump vs Conventional Coronary Artery Bypass Grafting: Early and 1-Year Graft Patency, Cost, and Quality-of-Life Outcomes

Abstract: OTIVATED BY MORBIDITY attributable to cardiopulmonary bypass, 1-3 US surgeons performed approximately 21% of coronary artery bypass operations off-pump in 2002. 4 Nonetheless, concern remains about the technical difficulty of off-pump coronary artery bypass (OPCAB), including the possibility of imprecise anastomoses and incomplete revascularization compromising patient outcomes. 5-9 Two prospective, randomized studies 10,11 and all but a few 12 retrospective comparisons have reported significantly fewer grafts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
7

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 510 publications
(92 citation statements)
references
References 43 publications
4
78
0
7
Order By: Relevance
“…Several studies compared the number of grafts compared to a preoperative plan. In most of these studies, no difference was found (8)(9)12,14,23), a few studies showed a difference in favour of CCABG, and one study found a difference in favour of OPCAB (24). In this study, however, the absolute number of grafts was 0.2 lower in the OPCAB-group.…”
Section: Graft Patencymentioning
confidence: 64%
See 2 more Smart Citations
“…Several studies compared the number of grafts compared to a preoperative plan. In most of these studies, no difference was found (8)(9)12,14,23), a few studies showed a difference in favour of CCABG, and one study found a difference in favour of OPCAB (24). In this study, however, the absolute number of grafts was 0.2 lower in the OPCAB-group.…”
Section: Graft Patencymentioning
confidence: 64%
“…Five years postoperatively 130/142 OPCAB-patients and 130/139 CCABG patients were alive (p=ns). Other studies with up to twelve months follow-up also failed to show any difference (7)(8)(9)(10)(11)(12)(13). Due to the relatively low risk of mortality associated with either operation, however, the statistical strength to detect any difference is not present in any of these studies.…”
Section: Long Term Survivalmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, a smaller fraction of OPCAB patients require inotropic or intra-aortic balloon pump support when compared to their propensity-matched CABG counterparts. A marked decrease in the need for transfusion of blood, platelets and fresh frozen plasma has also been noted (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Coronary Artery Bypass Grafting On Cardiopulmonary Bypass Ormentioning
confidence: 99%
“…Observational studies have demonstrated a significant increase in both retinal and cerebral microemboli following CPB (43-45). CPB has also been associated with increased cerebral emboli, inflammation and water content (43,(46)(47)(48) A randomized prospective trial comparing the results of OPCAB and CABG performed by a single, highly experienced surgeon demonstrated equivalent graft patency by coronary angiography at both initial discharge and 1 year following revascularization (34). Similarly, Nathoe and colleagues demonstrated equivalent graft patency between CABG and OPCAB 1 year following revascularization (60).…”
Section: Coronary Artery Bypass Grafting On Cardiopulmonary Bypass Ormentioning
confidence: 99%